Fair value of standing timber in the context of IAS 41 implementation: a case study with Pinus radiata - Acuña, Eduardo; Pinto, Antonio; Cancino, Jorge; Sandoval, Simón (Ciência Florestal, 2020)
Upon seeing the forest valuation in a knowledge-based framework and, although there are studies that indicate how the Chilean forestry companies evaluate their forestry assets, existing information can be inferred only on large and medium-sized enterprises; in the case of small enterprises there are no tangible data to know what the method of valuation of its assets. To provide a critical assessment of the valuation methods commonly used for the valuation of forests, this paper has two objectives. First, to evaluate compatibility of valuation criteria based on the fair value method of the biological assets of forest companies after adopting the International Financial Reporting System (IFRS), and second, to establish a method for the proper use of IAS 41 (International Accounting Standard) in the forestry sector through case studies in Chile. Fair value was determined according to IAS 41, in an immature plantation (eight years) established with Pinus radiata, using the “cost approach” and the “income approach”. The main findings suggest that the estimation of fair value using the “income approach” valuation method becomes more precise the younger the stand, i.e. calculating fair value based on the net present value of the stand, promises more accuracy. Nonetheless, the use of growth and yield simulation software for stands of exotic species, impede widespread use of this method. Results indicate the need to harmonize methodological criteria to measure fair value in crops of forest species.